2004
DOI: 10.1080/13607860410001709683
|View full text |Cite
|
Sign up to set email alerts
|

Well-being, appraisal, and coping in Latina and Caucasian female dementia caregivers: findings from the REACH study

Abstract: While there has been considerable interest in studying ethnically diverse family caregivers, few studies have investigated the influence of dementia caregiving on Latino families. The current study includes participants from two sites of the REACH (Resources for Enhancing Alzheimer's Caregiver Health) project to compare well-being, appraisal, and religiosity by ethnicity, with specific attention to levels of acculturation. Latina (n = 191) and Caucasian female (n = 229) dementia family caregivers from two regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(128 citation statements)
references
References 73 publications
4
123
0
1
Order By: Relevance
“…In the REACH study (level 3), anxiety levels in the Latin American female caregivers were not significantly different to those in White Americans, and did not differ with levels of acculturation (Coon et al, 2004); while African-American caregivers had lower levels of anxiety than White American caregivers (Haley et al, 2004;Roff et al, 2004;) and were less likely to use anxiolytic medication (Burgio et al, 2003). There were no differences between African and non-African-Americans in a smaller level-3 study (Knight et al, 2000;Knight and McCallum, 1998) involving over 150 CGs aged 50+ recruited from the local ADA, caregiver resource and counseling centers.…”
Section: Discussionmentioning
confidence: 55%
“…In the REACH study (level 3), anxiety levels in the Latin American female caregivers were not significantly different to those in White Americans, and did not differ with levels of acculturation (Coon et al, 2004); while African-American caregivers had lower levels of anxiety than White American caregivers (Haley et al, 2004;Roff et al, 2004;) and were less likely to use anxiolytic medication (Burgio et al, 2003). There were no differences between African and non-African-Americans in a smaller level-3 study (Knight et al, 2000;Knight and McCallum, 1998) involving over 150 CGs aged 50+ recruited from the local ADA, caregiver resource and counseling centers.…”
Section: Discussionmentioning
confidence: 55%
“…Caregiving is significantly associated with negative consequences for caregivers' psychological and physical health (e.g., Vitaliano, Zhang, & Scanlan, 2003), and different authors have found that intercultural differences exist in the degree to which caregiving results in distress (e.g., Coon et al, 2004;Knight et al, 2002). This circumstance has lead researchers to consider cultural values as an explanation of these differences.…”
Section: Introductionmentioning
confidence: 96%
“…Familism has been proposed as a value that may act as a protective factor against caregiving negative consequences (Coon et al, 2004). For example, Shurgot and Knight (2004) found a negative and significant association between familism and burden.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it becomes important to identify protective factors that may buffer the negative impacts of caregiving. Among the findings often reported in studies comparing the appraisal of caregiving by Hispanic versus Caucasian family caregivers is that the former report deriving greater gains and benefits from caregiving, and are less likely to describe the caregiving experience as bothersome, despite devoting more hours to caregiving each week, and having lower levels of income (Barber & Vega, 2004;Coon et al, 2004). Collectively, these findings have prompted some researchers to conclude that Hispanic caregivers embrace a cultural worldview of caregiving centered more on the positive outcomes and gains (Barber & Vega, 2004).…”
Section: Positive Appraisal and Social Support As Protective Factorsmentioning
confidence: 96%